FAKTOR UMUR, PARITAS, PENDIDIKAN DAN PEKERJAAN IBU BERSALIN TERHADAP KEJADIAN KPD - Hermina Humune (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
Premature rupture of membranes is rupture of the membranes before inpartum, opening <3cm in primigravida and multigravida <5cm. The incidence of KPD in Rati Melati Manukan Surabaya in 2012 (12.50%), in 2013 (15.74%), in 2014 (10.44%). The incidence of KPD is still high compared to the incidence of tolerance (8-10%). This study aims to determine the description of age, parity, education and maternity work on the incidence of KPD. Method: This research is descriptive. The population used was all maternity mothers in 2011 as many as 241 people with a total sample of 93 people selected using systematic random sampling. Secondary data collection from maternal cohort and labor report. The results of the study were made in the form of frequency distribution and cross tabulation. Results: The majority of KPD events occurred at age> 35 years (78.75%) compared to age 20-35 years (88.57%) did not experience KPD, grandemultipara parity (72.73) had a majority of KPDs compared to multiparas (78,72). did not experience KPD, low education (53.57%) the majority experienced KPD compared to higher education (100%) did not experience KPD, working mothers (32.08) the majority experienced KPD compared to those who did not work (77.50%) did not experience KPD. Discussion: there is still a high incidence of KPD caused by maternal characteristics. Therefore, midwives as health workers should be able to reduce the incidence of incidents by providing various counseling about reproductive age, safe parity for pregnancy and childbirth, providing care and IEC tailored to the mother's education, types of work that have the potential to cause complications for the mother.